Teachers’ professional identity in the digital world: A digital ethnography of religious education teachers’ engagement in online social space. - Robson, J (2014)
This thesis presents an ethnographic investigation of teachers’ peer-to-peer engagement in online social spaces, using the concept of teachers’ professional identity as a framework to shape and focus the study. Using Religious Education (RE) as a strong example of the wider phenomenon of teachers’ online engagement, three online social spaces (the Times Educational Supplement’s RE Forum, the National Association of Teachers of RE Facebook Page, and the Save RE Facebook Group) were investigated as case studies. A year was spent in these spaces with digital ethnographic research taking place simultaneously in each one. Data gathering primarily took the form of participant observations, in depth analysis of time-based sampled text (three 8-week samples from each space), online and offline narrative based interviews and, to a lesser extent, questionnaires, elite interviews and analysis of grey literature. The study finds that engagement in the online social spaces offered teachers opportunities to perform and construct their professional identities across a variety of topics ranging from local practical concerns to national political issues. In more practical topics the spaces could often be observed as acting as communities of practice in which professional learning took place and identities were constructed, with such online professional development influencing offline classroom practice. However, engaging across this spectrum of topics afforded users a broad conception of what it means to be a teacher, where professional identity was understood as going beyond classroom practice and integrating engagement with subject-wide, political and policy related issues at a national level. Such engagement provided many users with a feeling of belonging to a national community of peers, which, alongside political activism initiated in online interaction and meaning making debates concerning the future and identity of the subject, provided teachers with feelings of empowerment and a sense of ownership of their subject. However, the study found that teachers’ online engagement took place within structures embedded in the online social spaces that influenced and shaped engagement and the ways in which users’ professional identities were performed and constructed. These structures were linked with the design and technical affordances of the spaces, the agendas of the parent organisations that provided the spaces, and the discourses that dominated the spaces. These aspects of the spaces provided a structure that limited engagement, content and available online identity positions while additionally projecting ideal identity positions, distinctive in each space. These ideal identity positions had a constructive influence over many users who aspired to these ideals, often gaining confidence through expressing such socially validated ideals or feeling inadequate when failing to perform such ideal identity positions. Thus, this study finds a complex relationship between agency linked with active online identity performance and the constructive influence of embedded structures that contributed to the shaping of users’ engagement and their understandings of themselves as professionals and their subject.